Study on the Influence of Ca2＋ and Mg2＋ on the Properties of Zinc-Manganese Phosphate Coatings - LU Guojian, SUN Shenglong, ZHU Xiaohui, WANG Aixiang (Cailiao Baohu)
With the increasing environmental requirements， the zinc manganese nickel ternary phosphating process is strictly restricted due to nickel pollution， therefore， nickel-free phosphating technology for cathodic electrophoresis is receiving attention.In this study， Ca2＋and Mg2＋were used instead of Ni2＋， and the effects of Ca2＋and Mg2＋on the microstructure， film weight and dissolution rate of the phosphating film formed on cold-rolled plates were analyzed by XRD， SEM and other methods.The matching performance of the phosphating film with cathodic electrophoresis was also tested.It was shown that the grain size was refined by Ca2＋， the film thickness was increased by Mg2＋， and the resistance of the phosphating film to electrophoretic-paint dissolution was improved by the combined addition of Ca2＋and Mg2＋.The new zinc-manganese phosphating solution with added calcium and magnesium ions was found to have stable and controllable ion concentrations.After phosphating electrophoresis， the resulting coating was able to withstand a neutral salt-spray test for 800 h and met the requirement for cathodic electrophoretic coatings of a single-sided extension of 2 mm or less.